Respuesta :

Greetings from Brasil...

We will pass the - 2 to the 1st member

2 + [1/(X + 7)] = 15/(5(X + 7))

simplifying the numerator and denominator of the 2nd member

2 + [1/(X + 7)] = 3/(X + 7)

solving the sum of the 1st member

(2X + 15)/(X + 7) = 3/(X + 7)

product of the means by extremes

(2X + 15) · (X + 7) = 3 · (X + 7)

2X² + 15X + 14X + 105 = 3X + 21

2X² + 29X - 3X + 105 - 21 = 0

2X² + 26X + 84 = 0

solving this 2nd degree equation

Δ = b² - 4.a.c

Δ = 26² -  4 . 2 . 84

Δ = 676 - 4. 2 . 84

Δ = 4

X' = (-26 + √4)/2.2     X'' = (-26 - √4)/2.2

X' = -24 / 4     X'' = -28 / 4

X' = -6     X'' = -7

ACCESS MORE